Maverick. Season 2 [videorecording (DVD)] - Kelly, Jack, 1927-1992; Garner, James, 1928-2014; Moore, Roger, 1927-2017 (Warner Bros. Entertainment Inc., 2023)
Wisecracking ladies' man Bret Maverick and his no-nonsense brother Bart are on the loose in the wild frontier with a penchant for games when it comes to playing cards and falling in love. From one outpost to another, these handsome brothers have lady luck by their side. The deck is stacked against them as they tangle with card sharks, feuding families, killer cattlemen, crooked sheriffs, and more.